INCREASING STUDENT LEARNING CONCENTRATION IN WRITING USING PROJECT BASED LEARNING - Wulandari, Fitri (STKIP Muhammadiyah Pringsewu, 2019)
Based on the results of observations made on students of class IX.2 of SMP Muhammadiyah Pringsewu, the researchers found several symptoms that lead to the weak concentration of students. This study was focus on handling students' concentration problems in learning English, especially, in writing through Project Based Learning. It was Collaborative Action Research. The data collecting techniques used classroom observation, student reflection, and questionnaires. In analyzing the data, the researcher adopted Burns’ theory. The results showed that the use of Project Based Learning was able to improve the students’ learning concentration in writing activity.